2022
DOI: 10.1073/pnas.2205762119
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and rapid calcium intercalation into molybdenum vanadium oxides

Abstract: Looming concerns regarding scarcity, high prices, and safety threaten the long-term use of lithium in energy storage devices. Calcium has been explored in batteries because of its abundance and low cost, but the larger size and higher charge density of calcium ions relative to lithium impairs diffusion kinetics and cyclic stability. In this work, an aqueous calcium–ion battery is demonstrated using orthorhombic, trigonal, and tetragonal polymorphs of molybdenum vanadium oxide (MoVO) as a host for calcium ions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…Reproduced with under the terms of CC‐BY license. [ 23 ] Copyright 2022 the Author(s). Published by PNAS.…”
Section: Intercalation Materials For Multivalent‐ion Insertionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with under the terms of CC‐BY license. [ 23 ] Copyright 2022 the Author(s). Published by PNAS.…”
Section: Intercalation Materials For Multivalent‐ion Insertionmentioning
confidence: 99%
“…[19][20][21] Recent work has shown that open-tunnels are also ubiquitous in certain complex oxide materials [22] such as molybdenum vanadium oxides (Mo 3 VO x ) that exhibit pentagonal-, hexagonal-, and heptagonal-shaped tunnels. [22][23][24] Such open tunnels with large pores enable facile diffusion of multivalent ions. Especially, in an aqueous battery, ions along with its solvation sheath can get inserted.…”
Section: Intercalation Materials For Multivalent-ion Insertionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with other types of batteries, the development of CIBs is still in its primary stage due to a variety of challenges. First and most importantly, the search for cathode candidates that can store Ca 2+ ions in large capacity is a challenging task. , To date, only a limited choice of cathode materials have been identified to show feasible intercalation of Ca 2+ ions, including the open framework structure (i.e., Prussian blue, metal–organic compounds (MOCs), hexacyanoferrate , ), layered compounds (i.e., TiS 2 , α-MoO 3 , , α-V 2 O 5 , trigonal MoVO, Mg 0.25 V 2 O 5 ·H 2 O, Ca 0.28 V 2 O 5 ·H 2 O, CaV 6 O 16 ·2.8H 2 O), transitional metal oxides (i.e., CaMn 2 O 4 , CaCo 2 O 4 , Ca 0.4 MnO 2 ), polyanions (i.e., Na 1.5 VPO 4.8 F 0.7 ), and organic cathode material (PTCDA). The authors explored the calcium storage mechanism of these materials.…”
Section: Introductionmentioning
confidence: 99%